Current progress on the effect of mobile phone radiation on sperm quality: An updated systematic review and meta-analysis of human and animal studies. (1st August 2021) - Yu, Gang; Bai, Zhiming; Song, Chao; Cheng, Qing; Wang, Gang; Tang, Zeping; Yang, Sixing
Abstract: Potential suppression of fertility due to mobile phone radiation remains a focus of researchers. We conducted meta-analyses on the effects of mobile phone radiation on sperm quality using recent evidence and propose some perspectives on this issue. Using the MEDLINE/PubMed, Embase, WOS, CENTRAL, and ClinicalTrials.gov databases, we retrieved and screened studies published before December 2020 on the effects of mobile phone use/mobile phone RF-EMR on sperm quality. Thirty-nine studies were included. Data quality and general information of the studies were evaluated and recorded. Sperm quality data (density, motility, viability, morphology, and DFI) were compiled for further analyses, and we conducted subgroup, sensitivity, and publication bias analyses. The pooled results of human cross-sectional studies did not support an association of mobile phone use and a decline in sperm quality. Different study areas contributed to the heterogeneity of the studies. In East Europe and West Asia, mobile phone use was correlated with a decline in sperm density and motility. Mobile phone RF-EMR exposure could decrease the motility and viability of mature human sperm in vitro . The pooled results of animal studies showed that mobile phone RF-EMR exposure could suppress sperm motility and viability. Furthermore, it reduced sperm density in mice, in rats older than 10 weeks, and in rats restrained during exposure. Differences regarding age, modeling method, exposure device, and exposure time contributed to the heterogeneity of animal studies. Previous studies have extensively investigated and demonstrated the adverse effects of mobile phone radiation on sperm. In the future, new standardized criteria should be applied to evaluate potential effects of mobile phone RF-EMR dosages. Further sperm-related parameters at the functional and molecular levels as well as changes in biological characteristics of germ cells should be evaluated. Moreover, the impact of mobile phone RF-EMR on individual organs should also be examined. Graphical abstract: Image 1 Highlights: Mobile phone use was related to sperm quality decline of men in some areas. Mobile phone RF-EMR directly impaired mature sperm of men in vitro . Mobile phone RF-EMR affected some parameters of sperm quality in experiment animals. Experiment conditions affected pooled results of animal experiments. More studies should be conducted to investigate this issue in new era.